TUKIN PAYMENT ANALYSIS TO EMPLOYEES IN THE INFORMATION AND COMPLAINTS SERVICES OFFICE DIRECTORATE GENERAL OF TAXATION OF THE REPUBLIC OF INDONESIA - Sumarno Manrejo; Rinda Fitaningsih (Perbanas Institute, 2021)
This study aims to analyze the effect of providing performance allowances on employee performance in the Information Services and Complaints Office of the Directorate General of Taxes. The approach used is a quantitative approach with the type of correlation research. The population in this study were 378 employees with a total sample of 67 people based on random sampling. The technique of collecting data is by distributing questionnaires. The results show that performance allowances have a positive and significant effect on employee performance. Performance allowances can motivate employees to work optimally so that they can have an effect on improving employee performance at the Information and Complaints Service Office of the Directorate General of Taxes.